2021
DOI: 10.1245/s10434-021-10377-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patient Satisfaction and Quality of Life After Breast-Conserving Therapy: A Prospective Study Using the BREAST-Q

Abstract: Background Poor patient-reported satisfaction after breast-conserving therapy (BCT) has been associated with impaired health-related quality of life (HRQOL) and subsequent depression in retrospective analysis. This prospective cohort study aimed to assess the HRQOL of patients who have undergone BCT using the BREAST-Q, and to identify clinical risk factors for lower patient satisfaction. Methods Patients with primary breast cancer undergoing BCT were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Notably, our results also demonstrated a lack of correlation between complication rates and the average change between preoperative and postoperative BREAST-Q scores. These data can be extrapolated to suggest that adverse outcomes did not seem to outweigh the positive impact of reduction mammoplasty on QoL over time, which is reinforced by prior reports in the literature 18,22,35,36 . Still, prior studies have noted a negative relationship between complication rates and BREAST-Q satisfaction outcomes, 37 and future research delineating complications into major and minor categories could help clarify this association further.…”
Section: Discussionmentioning
confidence: 59%
“…Notably, our results also demonstrated a lack of correlation between complication rates and the average change between preoperative and postoperative BREAST-Q scores. These data can be extrapolated to suggest that adverse outcomes did not seem to outweigh the positive impact of reduction mammoplasty on QoL over time, which is reinforced by prior reports in the literature 18,22,35,36 . Still, prior studies have noted a negative relationship between complication rates and BREAST-Q satisfaction outcomes, 37 and future research delineating complications into major and minor categories could help clarify this association further.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, two additional themes relevant to patient QoL, “complementary and alternative medicine,” as well as the relationships between the patients and their relatives, were also identified, and the authors recommended incorporating these emerging subjects into existing QoL questionnaires [48]. Postoperative aesthetic outcome and body image perception, physical, social, sexual, and cognitive functioning also present crucial QoL aspects for BC patients [10, 49, 50]. These parameters could be further explored by analysing social media content, which would allow for country of origin and cultural background to be taken into account and in turn allow for relevant content to be offered to the appropriate patient groups [51].…”
Section: Benefitsmentioning
confidence: 99%
“…HRQOL has been extensively studied in western countries. These studies have found that BC survivors reported poor HRQOL with reduced physical and emotional function, and experienced major psychological symptoms relative to those without a cancer history [7,[9][10][11][12][13][14][15]. In addition, thesis studies have identi ed that age, socioeconomic status, disease stage and types of surgery, psychological factors and fear of recurrence may in uence perceptions of HRQOL [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that BC survivors reported poor HRQOL with reduced physical and emotional function, and experienced major psychological symptoms relative to those without a cancer history [7,[9][10][11][12][13][14][15]. In addition, thesis studies have identi ed that age, socioeconomic status, disease stage and types of surgery, psychological factors and fear of recurrence may in uence perceptions of HRQOL [9][10][11][12][13][14][15]. Unfortunately, ndings from the western population cannot be generalized to breast cancer women in the Arab populations, due to diversity in ethnicity, lifestyle and self-perception of the disease, social constraints, and other religious/cultural issues [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%